Primary Hyperaldosteronism Induced by Aldosterone-Producing Adenoma Co-Existing with A Left Suprarenal Accessory Spleen: Two Case Reports and A Review of The Literature - Li, Wen-Zhi; Wan, Xiang; Li, Long; Xu, Bin; wang, zhong (Urology Journal, 2019)
We encountered 2 patients (a 33-year-old woman and a 66-year-old man) with an aldosterone-producing adenoma (APA) and a left accessory spleen. The patients’ primary symptoms were hypertension and hypokalemia, and both had elevated serum aldosterone levels. Preoperative computed tomography a left suprarenal retroperitoneal mass and laparoscopic left adrenalectomy was performed in both cases. The postoperative microscopic examination revealed splenic tissue. Both patients experienced relief of their hypertension and hypokalemia, with an uneventful recovery.